The Hippo-Yes Association Protein Pathway in Liver Cancer - Lu Jie; Wang Fan; Dai Weiqi; Zhou Yingqun; Xu Ling; Shen Miao; Cheng Ping; Guo Chuanyong (Gastroenterology Research and Practice)
Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide and the third leading cause of cancer mortality. Despite continuing development of new therapies, prognosis for patients with HCC remains extremely poor. In recent years, control of organ size becomes a hot topic in HCC development. The Hippo signaling pathway has been delineated and shown to be critical in controlling organ size in both Drosophila and mammals. The Hippo kinase cascade, a singling pathway that antagonizes the transcriptional coactivator Yes-associated protein (YAP), plays an important role in animal organ size control by regulating cell proliferation and apoptosis rates. During HCC development, this pathway is likely inactivated in tumor initiated cells that escape suppressive constrain exerted by the surrounding normal tissue, thus allowing clonal expansion and tumor development. We have reviewed evolutionary changes in YAP as well as other components of the Hippo pathway and described the relationships between YAP genes and HCC. We also discuss regulation of transcription factors that are up- and downstream of YAP in liver cancer development.